Networks of Relationships of the City Notables in the Ottoman Sharia Court: “Muzakkis, Shuhûd al-hal and Muslihun” - Akman, Ekrem (Journal of Ecohumanism, 2025)
In Ottoman urban life, the judge and the sharia court Formed the center of social networks. In the functioning of the sharia court, testimony of the witnesses is the foundation of the judicial procedure. Aside of the witnesses of the incident, there is also a class referred to as the notables(eşraf), who are known by different names, consisting of the city's respected and upright Muslims known for the sharia court . These are the classes called just witnesses(adil şahitlar), validators (muzakkiler), witnesses of the incident (şühûdu'l-hal) and mediators (muslihun), who are included in the records during the trial process. This class, defined in the records as the peomin Figures of the city (vücuh), the respected of the realm(muteberân-I memleket), and the arbiters of the town, constitutes the court’s social periphery. The subject of the article is to trace the class seen in the records with their roles in the sharia trial processes, which are at the center of urban social life in the Ottoman/Islamic city. These are the civil mediators, those who take part in the investigation of the witnesses, and the respected part of the city who participate in the process by signing the verdict in the role of spectators in the court. Examining The status and relations of this social class, called the arbiters or notables in the Ottoman city from the perspective of the court environment, are important in terms of urban studies. The article investigates the identities of the mentioned class -muzekkiler, şühûdu'l-hal and muslihun-, their status in society, and their roles in the court and in the trial process. The sharia records were used as the main source in the study. In the context of the records scanned as primary sources, it was aimed to reveal the duties or roles of the mentioned social class in the court, their relations with the judge and the court, and their position and status in the urban social life of the city..